Politics, government health expenditure and infant mortality: does political party orientation matter? - Alexiou, Constantinos; Trachanas, Emmanouil (Emerald, 2021)
Purpose Motivated by the scant available evidence, this paper explores the relationship between government political party orientation and infant mortality. Design/methodology/approach A panel quantile methodology is applied to a data set that consists of 15 countries of the G20 group over the period 2000–2018. The authors control for heterogeneous parameters across countries and quantiles and obtain estimates across the different points of the conditional distribution of the dependent variable. Findings The findings support the hypothesis that political party orientation has a significant effect on a population health indicator such as infant mortality. The analysis suggests that, to a great extent, left-wing government parties contribute to better health outcomes – when compared to right and centre political parties – both individually as well as interacted with government health expenditure. Moreover, the impact of redistributing policies appears to be of a paramount importance in alleviating infant mortality, while more education and lower unemployment can also contribute to better health outcomes. Originality/value The authors explore the relationship between the nature of government political party orientation (i.e. right, centre and left) and infant mortality whilst at the same time gauging the mediating effect of party orientation via government health expenditure on infant mortality. Additional aspects of the impact of other control variables, such as income inequality, unemployment and education on infant mortality are also investigated.
Keywords: Health expenditure; Infant mortality; Panel data